A study on the personal data processing and the UCPD focused on Italy, Germany and the UK. Issue 1 (February 2021) - Nišević, Maja
Manipulation with Big Data Analytics allows commercial exploitation of individuals based on unfair commercial practices. Consequently, the concepts of consumer protection are essential in the data-driven economy and a central issue for effective safety for individuals in the Big Data Age. Although the fields of consumer protection and data protection in the European Union (EU) have developed separately, there is an unambiguous relationship between them. While the GDPR plays a crucial role in an individual's data protection in a case of personal data processing, Directive 2005/29/EC (UCPD) plays an essential role in regulating an individual's protection from the unfair commercial practice when it comes to personal data processing. A vital aspect of the UCPD is the enforcement of issues related to consumer privacy. However, a much-debated question is whether the UCPD is fully effective or not when it comes to personal data processing. This paper examines case law examples on WhatsApp and Facebook in Italy, Germany and the United Kingdom. This paper also aims to come to a conclusion on the issue of the applicability of the rules on unfair commercial practice when it comes to data processing.